PENGARUH PELATIHAN KERJA, PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI YAYASAN KESEJAHTERAAN UMAT PERSADA INDONESIA - Umi Daimatul Muaddabah; Burhanudin Ahamd Yani; Supawi Pawenang (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study is whether job training, career development and work environment have a significant and simultaneous effect on employee performance at Persada Indonesia's Persada Welfare Foundation. The population in this study came from the number of employees who worked, namely 43 people. The research sample was taken by incidental sampling and obtained 43 respondents with multiple linear regression methods. In this study, using a questionnaire that was distributed to the employees encountered. The results showed that the variables of job training, career development and work environment had a significant effect on employee performance at the Persada Persada Indonesia Welfare Foundation, either partially or simultaneously. Three independent variables explained that the employee's performance was 67.9% and the others were influenced by other variables Keywords: job training, career development and work environment, employee performance